Expert System Mengatasi Anxiety Disorder Pada Mahasiswa Dalam Menghadapi Tugas Akhir Metode Backward Chaining - Indah Risfia; Dewi Maharani; Muthia Dewi (STMIK Budi Darma, 2022)
Anxiety Disorder is a psychological disorder that can be experienced characterized by the emergence of various symptoms which cause the sufferer to experience anxiety that is so great and excessive that it is very possible to affect the sufferer psychologically or physically. The obstacles that are most often experienced by final year students in completing their final assignments are the emergence of excessive feelings of anxiety, feeling restless, easily tired, difficult to concentrate, empty thoughts. irritability, muscle tension, difficulty sleeping, cold fingers, faster heart rate, cold sweats, headache, decreased appetite, sleeplessness and chest tightness which is often referred to as Anxiety Disorder. The relevance of computerization and technology in expert systems in diagnosing anxiety disorders in final year students is needed to help students find solutions to their problems. Therefore we need a method that can assist the analysis of the expert system design that will be made in this study, namely the Backward chaining method. Backward Chaining is an inference method that works backwards towards the initial conditions. The process starts from the Goal (which is in the THEN section and the IF-THEN rule), then the search starts to run to match whether the facts match the premises in the IF section. This technological advancement can help transfer human understanding into a system form so that it can be used by many people and is not limited by time without replacing the role of humans.